Microstructure of Electrodeposited Lithium Metal Electrodes in Reservoir-Free Solid-State Batteries - Becker, Juri Jonathan Erwin; Justus Liebig University Giessen (My University, 2026)
The transition towards renewable energy sources and the electrification of transportation are essential drivers for the development of advanced energy storage solutions with high energy and power densities. Conventional lithium-ion batteries based on liquid electrolytes have become the dominant technology for portable electronics and electric vehicles. However, they are rapidly approaching their theoretical physicochemical limits in terms of energy density. Solid-state batteries comprising lithium metal electrodes and inorganic solid electrolytes promise substantial improvements over conventional lithium-ion batteries, offering the potential to overcome current safety concerns, mitigate flammability risks inherent to liquid electrolytes, and increase both energy as well as power density. A critical obstacle in implementing lithium metal electrodes remains the maintenance of the electrode|solid electrolyte interface during cell operation, which can lead to morphological instabilities during both charge and discharge. Furthermore, the storage of lithium metal and cell manufacturing must take place under inert gas atmospheres, which is costly. Otherwise, contact with atmospheric components such as moisture (H2O), oxygen (O2), and nitrogen (N2) leads to the formation of resistive passivation layers on the surface, which impede cell performance. To address these challenges, reservoir-free cell concepts are being intensively explored. In these configurations, the lithium metal electrode is electrodeposited only during the initial charging step, with lithium sourced from the lithiated positive electrode. This approach substantially simplifies cell fabrication, as no lithium metal needs to be handled during assembly. However, electrodeposition is likewise associated with new morphological instabilities, and fundamental differences in microstructure and chemistry between conventionally produced and electrodeposited lithium remain insufficiently understood. This dissertation focuses on the chemical and microstructural characterization of electrodeposited lithium, using reservoir-free model systems comprising steel|Li6PS5Cl interfaces. Chemical analysis revealed an exceptionally high purity compared to commercial lithium foils. Microstructural analysis on millimeter-sized cross-sections, based on electron backscatter diffraction, uncovered a dynamic evolution of the resulting lithium grain structure during both electrodeposition and subsequent electrodissolution cycles. Finally, interlayer materials were introduced as an effective measure to control the resulting lithium microstructure. Overall, the results presented in this dissertation significantly expand the understanding of electrodeposited lithium layers both in terms of their purity as well as their microstructure. Latter depends on electrodeposition parameters, cycling history, and current collector modifications. These insights aim to optimize the performance of reservoir-free cells and enable the development of advanced solid-state batteries.
Mikrostruktur von elektrochemisch abgeschiedenen Lithiummetallelektroden in Reservoir-freien Feststoffbatterien
Keywords: Lithium metal electrodes; Reservoir-free solid-state batteries; Microstructure; ddc:500; ddc:530; ddc:540